Evaluation of fluorinated phospholipid analogs: A study on ADMET profiles, molecular docking and dynamics simulation in anticancer therapy - Saqib Ishaq; Obaid Habib; Abdul Aziz; Raheel Tahir; Hira Mushtaq; Said Hassan; Sarah Sarwar; Mohammad S. Mubarak; Ajaz Ahmad; Amin Ullah (Heliyon)
Fluorinated phospholipid analogs Edelfosine and Ilmofosine drug reveal expressive potential as antineoplastic factors though targeted interaction with heat shock protein (HSP70KDa1A), an essential mediator in cancer pathophysiology. Using evolved computational approaches, this research evaluated their ADMET (absorption, distribution, metabolism, excretion and toxicity) profiles receptor binding affinities and molecular dynamics. Molecular docking discernible vigorous interactions with Edelfosine drug displaying greater binding stability and consistent hydrogen bonding as confirmed by 100 ns molecular dynamics simulations. Comparative interpretation emphasized Edelfosine drug enhanced pharmacokinetic properties depicted by lower RMSD values, stable solvent-accessible surface area and reduced structural fluctuations relative to Ilmofosine drug. Functional annotation and phylogenetic investigation affirmed the evolutionary conservation and pivotal biological function of heat shock protein (HSP70KDa1A). These findings position Edelfosine drug as a promising candidate for targeted cancer therapy appropriated further experimental validation to elucidate its mechanisms of action and therapeutic efficacy.